Active provisioning of food to host sea anemones by anemonefish - Yuya Kobayashi; Yuki Kondo; Masanori Kohda; Satoshi Awata (Scientific Reports)
Abstract In mutualistic symbiosis, organisms often provide food to their partners. However, the processes and significance of food provisioning to hosts remain poorly understood. The anemonefish Amphiprion clarkii, which prefers larger hosts, has been suggested to provide food to its host the sea anemone Entacmaea quadricolor. In the present study, we investigated food provisioning by anemonefish and its effects on the symbiotic relationships. When given foods of various sizes and types in the field, anemonefish selectively consumed small animal food (krill, clams, squid, and fish) and green macroalgae of small size, while providing larger pieces of animal food to their hosts. Additionally, the anemonefish avoided either eating or providing brown macroalgae and sponges to the host anemone, which appeared to be unsuitable as food for both anemonefish and sea anemones. When repeatedly provided small pieces of animal food, the anemonefish initially consumed the food themselves, but upon satiety, increased provisioning to the host. Food provisioning positively influenced the growth of host anemones. These findings suggest that anemonefish actively provide food to host anemones based on the situation, adding to our knowledge of the mutual benefits of symbiosis among partners.